ANALISIS KINERJA BADAN KEPEGAWAIAN, PENDIDIKAN DAN PELATIHAN DAERAH KABUPATEN KOTABARU DALAM PENYELENGGARAAN PELAYANAN KEPEGAWAIAN - Ade Hermawan; Widarto Widarto (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2020)
The purpose of this study is to analyze the Performance of the Regional Civil Service, Education and Training Agency of Kotabaru Regency in the provision of services in the field of staffing, education and training to all civil servants in the Regency Government based on indicators of Productivity, service quality and accountability are in the category of Good Enough . The Performance of the Regional Civil Service, Education and Training Agency in the District of Kotabaru in the provision of services in the field of staffing, education and training to all civil servants within the Regency Government is influenced by factors in the availability of reliable Human Resources (HR), facilities and infrastructure, proportional budget and adequate.